Beethoven's Compositional Choices: The Two Versions of Opus 18, No 1, First Movement - Levy, Janet M. (Philadelphia Univ of Pennsylvania Press, 1982)
For musical experts. A detailed analysis of the first movement of string quartet Op.18, No.1. Excellent study for students of Beethoven, composition, or string quartet players. Musical examples on nearly every page. Large format, beautifully bound.